Ecuadorian Political System: Tension in the context of the COVID 19 (March-May 2020) - Carina V. Ganuza (Technium Social Sciences Journal, 2020)
The Ecuadorian political system represented by President Lenin Moreno has caused an atmosphere of constant tension in the face of the spread of COVID 19, leading to a setting of greater disturbance as the health crisis situation, that was used to apply neoliberal measuresthat had been suspended in October 2019, in the setting of massive protests and discontent. This work is a case study that analyzes the decisions made by the Moreno administration in the face of the pandemic in the temporary cutback that took place during the months of March and May of 2020, a clear move to take advantage of the health crisis situation, and in order to complete its decisions regarding austerity and budget cutbacks. It is, thus, inferred that there is a loss of the sense of protection of life as a primary constitutional right.